Enhance English communication skill through KTP Kindy Program - Nor Salwana, Mohammad Idris (2017)
In its effort to increase the English communication skill amongst the TASKA child-care worker, Centre for Modern Languages and Human Sciences (CMLHS) together with Persatuan Pengasuh Negeri Pahang (PPNP) organized a workshop entitled KTP Kindy Workshop: Communication English & Effective Storytelling Techniques for Daycare Educators.